Internal Fixation of Femoral Neck Fractures in the Dog -an in vitro Study - Lambrechts, N. E.; Verstraete, F. J.M.; Sumner-Smith, G.; Raath, A.D.; van der Linde, M.J.; Groeneveld, H. T. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The in vitro performances of four recognized fixation methods of femur neck fractures in the dog were evaluated. After a simulated basilar fracture, three multiple pin techniques and a lag screw method were applied to four groups of nine freshly dissected femurs. A standardized force was applied to all specimens as well as five intact femurs and the force-deformation curve and yield points were recorded. Radiographs were taken to determine the mode of failure. The results indicate that the lag screw and three-parallel-pin techniques were significantly stronger than the two-pin methods. The pin techniques failed by either bending and/or slippage, while the lag screw failed by bending and/or pulling in of the screw head into the lateral femoral cortex.An in vitro study, comparing the mechanical performances of four fixation techniques for femoral neck fracture fixation, is presented. The lag screw and three-pin techniques were stronger than the two double-pin techniques. Fixation failure occurred through bending or slippage of the pins, or through bending of the screws or pulling of the screw head into the lateral femoral cortex.
Keywords: Dog; femoral neck; fracture; fixation; in vitro study